MARKERS OF INFLAMMATION IN CHRONIC KIDNEY DISEASE PATIENTS WITH ARTERIAL HYPERTENSION AND OBESITY - Капустник, В.А.; Shelest, B.; Kovaliyova, Yu.; Shelest, O. (World of Medicine and Biology, 2014)
The work is based on the results of the survey of 56 patients with chronic kidney disease (CKD) II-III stages (chronic glomerulonephritis and pyelonephritis) with hypertension II stage and with obesity and without it. The analyze of changes of such parameters as C-reactive protein, tumor necrosis factor-α, IL-lβ, IL-4 are presented in CKD patients without hypertension and on the background of high blood pressure and with different types of body weight. The nature of the impact of inflammation of hypertension in patients with chronic kidney disease with high blood pressure and obesity was established. In the study it was revealed a direct correlation between hypertension and obesity and the severity of inflammation in patients with chronic kidney disease.